2004
DOI: 10.1007/s11882-004-0048-7
|View full text |Cite
|
Sign up to set email alerts
|

Chemokines in inflammatory bowel disease

Abstract: Ulcerative colitis (UC) and Crohn's disease (CD), collectively termed inflammatory bowel diseases (IBD), represent chronic relapsing and remitting inflammatory disorders of the gastrointestinal tract that are characterized by leukocytic infiltration of the intestinal mucosa and submucosa. In CD, the inflammation is transmural and frequently associated with granuloma formation. Chemokines have emerged as the most important regulators of leukocyte trafficking during infection or inflammation and, therefore, have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
54
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 68 publications
2
54
0
Order By: Relevance
“…It has previously been reported that not only is chemokine expression up-regulated during active colitis, but that chemokines are involved in disease initiation and progression (38). In our own microarray studies presented here, it is clear that IEC greatly upregulate expression of a number of chemokine genes, including CCL7 and CXCL5.…”
Section: Discussionsupporting
confidence: 57%
“…It has previously been reported that not only is chemokine expression up-regulated during active colitis, but that chemokines are involved in disease initiation and progression (38). In our own microarray studies presented here, it is clear that IEC greatly upregulate expression of a number of chemokine genes, including CCL7 and CXCL5.…”
Section: Discussionsupporting
confidence: 57%
“…It is possible that these cells were recruited from the peripheral blood by chemokines such as MIP3␣/CCL20, released from nonimmune tissue cells, similar to the observations made with models of inflammatory bowel disease (24) or pulmonary inflammation (22,25). DCs migrated to the target eye before the host B or T cells, reaching a peak on day 4 and declining slightly on day 7.…”
Section: Discussionmentioning
confidence: 64%
“…Substance P is known to activate resident macrophages to release proinflammatory cytokines, such as TNF-␣, which may then recruit the surrounding circular muscle cells to amplify the secretion of specific inflammatory mediators. Thus neuronal reflexes and increased circulating levels of proinflammatory cytokines (24) may induce a fullblown inflammation-like response in the muscularis externa, without the infiltration and activation of lymphocytes seen in patients with ulcerative colitis (32). The circular smooth muscle contractility in these patients is suppressed without any apparent presence and activation of immune cells in the muscle layers (45).…”
Section: Discussionmentioning
confidence: 99%